Intelligent analysis and data visualisation for teacher assistance tools: The case of exploratory learning. (16th September 2019) - Mavrikis, Manolis; Geraniou, Eirini; Gutierrez Santos, Sergio; Poulovassilis, Alexandra
Abstract: While it is commonly accepted that Learning Analytics (LA) tools can support teachers' awareness and classroom orchestration, not all forms of pedagogy are congruent to the types of data generated by digital technologies or the algorithms used to analyse them. One such pedagogy that has been so far underserved by LA is exploratory learning, exemplified by tools such as simulators, virtual labs, microworlds and some interactive educational games. This paper argues that the combination of intelligent analysis of interaction data from such an Exploratory Learning Environment (ELE) and the targeted design of visualisations has the benefit of supporting classroom orchestration and consequently enabling the adoption of this pedagogy to the classroom. We present a case study of LA in the context of an ELE supporting the learning of algebra. We focus on the formative qualitative evaluation of a suite of Teacher Assistance tools. We draw conclusions relating to the value of the tools to teachers and reflect with transferable lessons for future related work. Practitioner Notes What is already known about this topic Learning Analytics (LA) tools can support teachers' orchestration but most of the work so far has focus mostly on instructionist pedagogies or Computer‐Supported Collaborative Learning. Exploratory Learning Environments (ELEs) encourage students to freely explore a domain and follow a variety of solutions and have the potential to lead to more engagement and deeper learning. The freedom in ELEs introduces orchestration challenges that hinder the adoption of such pedagogies in classroom. What this paper adds A set of usage scenarios for LA tools for exploratory environments derived from teacher input and design and methodological guidelines based on a reflection from the study. Showcases a suite of Teacher Assistance tools purposefully designed for teachers' orchestration requirements during Exploratory Learning. Empirical evidence of the perceived usefulness of these tools and feedback from a large number of teachers thanks to a methodology of re‐using previously collected classroom data. Implications for practice and/or policy A methodology for involving teachers in the design and evaluation of LA. Highlights teacher training needs for LA. Teachers should be provided with tools that help them orchestrate different activities including ones with digital tools underpinned by a constructionist pedagogy.